Aldosterone-Mineralocorticoid Receptor - Cell Biology to Translational Medicine 2019
DOI: 10.5772/intechopen.87234
|View full text |Cite
|
Sign up to set email alerts
|

MR/GR Signaling in the Brain during the Stress Response

Abstract: This contribution is about mineralocorticoid receptors (MRs) in their capacity as mediators of glucocorticoid action in the brain. This paradox has evolved because MRs are promiscuous and bind with high-affinity cortisol and corticosterone as well as aldosterone, deoxycorticosterone, and progesterone. The MRs "see," however, predominantly glucocorticoids, because of their 100-1000-fold excess over aldosterone; bioavailability is further enhanced because of local regeneration of glucocorticoids by 11βOH-steroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…Acute stress increases the level of corticosterone and subsequently activates two adrenal steroid receptors, namely, GRs and MRs, both of which induce the alteration of synaptic transmission via nongenomic and genomic pathways ( de Kloet and Meijer, 2019 ). In this study, we found that acute stress decreased the ratio of sEPSCs to sIPSCs with an increasing trend in the sIPSC amplitude and a decreasing trend in the sEPSC amplitude ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Acute stress increases the level of corticosterone and subsequently activates two adrenal steroid receptors, namely, GRs and MRs, both of which induce the alteration of synaptic transmission via nongenomic and genomic pathways ( de Kloet and Meijer, 2019 ). In this study, we found that acute stress decreased the ratio of sEPSCs to sIPSCs with an increasing trend in the sIPSC amplitude and a decreasing trend in the sEPSC amplitude ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MRs and GRs form a tightly co-regulated network that coordinates stress response and this observation led to the genesis of MR/GR balance hypothesis [ 30 ]. According to this hypothesis, an imbalance between the effects of GRs and MRs during the stress response may lead to dysregulation of the HPA axis and an inability to adapt to stressors and restore homeostasis, thereby conferring an increased vulnerability to a number of stress-related disorders [ 45 ].…”
Section: Functional Synergistic Network Of Mr and Grmentioning
confidence: 99%
“…Under normal conditions, low-levels of CORT mainly binds to and activates MRs (see Ogita et al, 2012 ; Mifsud and Reul, 2018 ), but during periods of stress, CORT increases to high enough levels that it activates GRs. GRs are expressed on cells throughout the brain, but are heavily expressed on cells in the hippocampus (de Kloet et al, 1993 ; de Kloet and Meijer, 2019 ). The hippocampus is believed to be especially vulnerable to stress because it contains one of the highest densities of GRs in the brain (Joels et al, 2018 ).…”
Section: Hippocampus Overviewmentioning
confidence: 99%